A Study on the Interplay between Creativity and Aggression in Secondary School Student - Naveed, Tayyaba; Chethiyar, Saralah Devi Mariamdaran; Arshad, Muhammad Zulqarnain (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
The purpose of this study is to evaluate, among secondary school students, whether or whether there is a connection between creative expression and aggressive behavior. Purposive random selection was used to choose students for the study from two secondary schools located in Sahiwal city: Government Girls Model Pilot Secondary School and Lasani public school. The total number of students that participated in the study was one hundred. The Creative Personality Scale (CPS) and the Buss-Perry Aggression Questionnaire were applied in this study so that the researchers could examine the association between creativity and aggression. The data suggest that there is an inverse relationship between creative output and aggressive behavior among secondary school pupils. However, there was no discernible gap found between the sexes in terms of creative output. In addition, the findings of the study indicate that male students are more likely to engage in aggressive behavior than their female counterparts. In addition, the findings indicate that students in government and private schools’ 10th grade, who are aged 16 to 18, are more creative than students in government and private schools’ 9th grade, who are aged 13 to 15.